James Kelman. - Kovesi, Simon (Contemporary British novelists., 2007)
James Kelman is Scotland?s most influential contemporary prose artist. This is the first book-length study of his groundbreaking novels, and it analyses and contextualises each in detail. It argues that while Kelman offers a coherent and consistent vision of the world, each novel should be read as a distinct literary response to particular aspects of contemporary working-class language and culture. Richly historicised through diverse contexts such as Scottish socialism, public transport, emigration,?Booker Prize? culture and Glasgow?s controversial?City of Culture? status in 1990, Simon Kove.